Development of mathematical models for the determination of total solids in whey (Research, Society and Development, 2022)
The objective of this study was to develop mathematical models for the indirect calculation of the dry matter content of whey. The indirect determination of the dry matter is faster, requires less complex analysis and presents data similar to the gravimetric reference method (oven drying). The dry matter of whey contains fat, proteins, minerals and lactose, which have a high technological value and make the quantification of the dry extract important to quantify the (techno-economical) value of the whey and verify that the whey is within the norms. To develop the mathematical models, seventeen samples of whey obtained by coagulation of pasteurized whole milk and seventeen obtained by coagulation of pasteurized skim milk were analyzed. The whey samples were analyzed for pH, fat, density, soluble solids and total solids by the direct method. Thus, three equations were developed for calculating the dry matter of whey through fat, density and moisture data: one for whey from whole milk, one for whey from skimmed milk and one that covered both types of whey. It was found that there was no significant difference between the means of dry matter obtained by direct and indirect methods for the three groups of whey considered a Student's t test at a 5% significance level. It was concluded that the indirect method is an alternative to be used for sweet whey, considering the reliability of the results and the shorter time required to obtain those results compared to the direct method.